Impact of Fundamental Factors on Stock Returns in FTSE 100 - Leong, JiaJun (2020)
Over the past decade, with the transition in economy, stock market has gained a tremendous popularity from the public. Majority of investors today are retail investors who seeks to outsmart the market in order to profit. This study aims to use panel data to study the relationship between fundamental factors and stock returns. Model wise, both common effect model and random effects model are much alike in terms of coefficient signs and significant. As for fixed effect model, the variables have a much stronger explanatory power compared to random effect model. After 3 series of test, fixed effect model was found to be the best model for this study.